Java programs to accompany Programming logic and design - Smith, Jo Ann (Cengage Learning, 2015)
This book helps you learn how to use Java to transform program logic and design into working programs. This book combines the power of Java with the popular, language-independent, logical approach of the Programming Logic And Design text